2014
DOI: 10.1111/iju.12513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propiverine hydrochloride on stress urinary incontinence

Abstract: Abbreviations & AcronymsObjectives: To investigate whether the anticholinergic agent, propiverine hydrochloride, is clinically effective for stress urinary incontinence. Methods: The participants were adult female patients with the chief complaint of stress incontinence. Propiverine (20 mg once daily) was given for 8 weeks. If the response was inadequate after 4 weeks of treatment, the dose was increased to 40 mg/day. Before and after 4 and 8 weeks of treatment, lower urinary tract symptoms were assessed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…These findings were consistent with their previous report that propiverine supplementation (5 mg/mL/day for 2 weeks) increased the urethral baseline pressure, whereas imidafenacin (an anticholinergic agent, 0.01 mg/mL/day) did not show such an increased response. 5 Regarding the mechanism and site of action of propiverine based on the current and previous results, it is conceivable that an increase of noradrenaline induced by propiverine can activate both sympathetic pathways and Onuf's nucleus through a1-adrenergic receptors to increase the urethral baseline pressure and LPP. These mechanisms might be reasonable to ameliorate SUI, and propiverine could be a promising tool for the treatment of SUI.…”
Section: Editorial Commentmentioning
confidence: 86%
See 2 more Smart Citations
“…These findings were consistent with their previous report that propiverine supplementation (5 mg/mL/day for 2 weeks) increased the urethral baseline pressure, whereas imidafenacin (an anticholinergic agent, 0.01 mg/mL/day) did not show such an increased response. 5 Regarding the mechanism and site of action of propiverine based on the current and previous results, it is conceivable that an increase of noradrenaline induced by propiverine can activate both sympathetic pathways and Onuf's nucleus through a1-adrenergic receptors to increase the urethral baseline pressure and LPP. These mechanisms might be reasonable to ameliorate SUI, and propiverine could be a promising tool for the treatment of SUI.…”
Section: Editorial Commentmentioning
confidence: 86%
“…4 Interestingly, previous manuscripts have reported the efficacy of propiverine, an anticholinergic drug with calcium antagonistic action, against pure SUI patients in Japan. 5 In the present study, Nishijima et al tried to investigate the mechanism through which propiverine is effective for treating SUI. 6 The authors found that intravenous injection of propiverine increased the leak point pressure in rats with vaginal distention.…”
Section: Editorial Commentmentioning
confidence: 94%
See 1 more Smart Citation
“…Propiverine hydrochloride (referred to in the following as propiverine) has been shown to combine both anticholinergic and calcium channel blocking actions and reported to be effective for the treatment of stress incontinence as well as detrusor overactivity [5]. In daily practice, propiverine, an anticholinergic drug indicated for urge incontinence, is given to patients who have both urge incontinence and stress incontinence [5].…”
Section: Introductionmentioning
confidence: 99%
“…In daily practice, propiverine, an anticholinergic drug indicated for urge incontinence, is given to patients who have both urge incontinence and stress incontinence [5].…”
Section: Introductionmentioning
confidence: 99%